Reducing the Mutual Coupling of Cylindrical Circular Microstrip Antennas (CCMAs) Array Using EBG Structure (Baghdad Science Journal, 2023)
A theoretical study to design a conformal microstrip antennas was introduced in this work. Conformal microstrip antennas define antennas which can be conformed to a certain shape or to any curved surface. It is used in high-speed trains, aircraft, defense and navigation systems, landing gear and various communications systems, as well as in body wearable. Conformal antennas have some advantages such as a wider-angle coverage compared to flat antennas and low radar cross-sectional (RCS) and they are suitable for using in Radome. The main disadvantage of these antennas is the narrow bandwidth. The FDTD method is extremely useful in simulating complicated structures because it allows for direct integration of Maxwell's equations depending on time. The 1x2 cylindrical circular microstrip antennas array is designed and simulated vertically via Finite Difference Time Domain (FDTD) method where can directive antenna be achieved through antennas array design. Mutual coupling between the antennas in the array and the different separation between them were studied. The circular patch is excited by a probe feed method for several reasons including providing less spurious radiation from the probe current, in addition to the simplicity in theoretical engineering installation and practical manufacturing. It is well known that the values of the coupling are decreased as the distance separation increased. Cylindrical circular microstrip antenna with resonant frequency operating is 3.5GHz for  mode, several parameters like return loss, band width, and input impedance are calculated. Also, for isolated coupling, mutual coupling coefficients, directivity gain, for different separations between the centers of the two adjacent circular patches in terms the wave length operating are calculated. Moreover, the electromagnetic band gap EBG structure is used for reducing the mutual coupling created by the surface waves in order to enhance the antenna's performance in an array has become smaller than before. The proposed EBG is a three triangular-shape equal sides metallic structure, utilizing the inter-element spacing in an array. The less value of   for the spacing between the two centers of patches is . BW percentage increased to 34.3% and the directivity is enhanced also.  Additionally, simulations were done using MATLAB 2017b.